Performance Analysis Of Queue Management Algorithms in NS-3 Network Simulator - Ünal Çavuşoğlu; Muhammed Maruf Öztürk; Ahmet Zengin; Uğur Özbek (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2013)

(untitled)
In this article, which has an important role in the regulation of the flow of traffic in computer networks is discussed queue management. Queue management algorithms are widely used today introduced the working principles are described briefly. NS-3 network simulator program was used for queue management algorithms comparison of performance. On NS-3 network simulator, DROP TAIL and RED queue management algorithms have been tested on various topologies and performance evaluations were made. Furthermore, the studies are compared with results obtained previously. The data obtained from these tests and studies those evaluated, RED algorithms that use probabilistic methods and threshold values have been found to be more successful.